Recovery of Alcohol Ethoxylates Nonionic Surfactant using Co-Current Vacuum Stripping - Kungsanan, Suratsawadee; Kittisrisawai, Sirinthip; Kitiyanan, Boonyarach; Rirksomboon, Thirasak; Osuwan, Somchai; Scamehorn, John F. (ASEAN Journal of Chemical Engineering, 2011)
Cloud point extraction (CPE) has shown to be an effective technique to remove organic compounds from contaminated water using nonionic surfactant as a separating agent. To make this process more economically attractive, the spent nonionic surfactants should be recycled and reused. This work utilized a packed column operated under vacuum in co-current mode to remove the volatile organic compounds (VOCs) from the secondary alcohol ethoxylates, AEs, coacervate solution. The co-current operation can effectively avoid plugging, excessive foaming, and flooding. The selected volatile organic contaminants are aromatic hydrocarbons such as benzene, toluene, and ethylbenzene. The hydrophobic properties of the VOCs are described by an octanol-water partition coefficient (Kow). The results show that as the Kow increases, the Ks substantially increases while the Happ of the VOCs significantly decreases. The reduction of VOCs volatilization is possibly due to greater partitioning of the VOCs into surfactant micelles. The similar trend is also observed in the continuous operation. The results show that as the Kow increases, the percentage of VOCs removal and the Kxa decrease due to the VOCs’ hydrophobic effect. The removal percentages of the VOCs vary from 60 to 90%. The R2 of the log-log and semi-log relationships between Kow and studied parameters are observed in the range of 0.96-0.99.